A rare 8q24 single nucleotide polymorphism (SNP) predisposes North American men to prostate cancer and possibly more aggressive disease. (25th September 2014) - Grin, Boris; Loeb, Stacy; Roehl, Kim; Cooper, Phillip R.; Catalona, William J.; Helfand, Brian T.
<x xml:space="preserve">Abstract</x> Objective To assess the frequency of a novel prostate cancer‐associated single nucleotide polymorphism (SNP), rs188140481, in a North American population and to evaluate the clinical significance of this variant including annotated prostatectomy pathology. Patients/Subjects and Methods We examined the frequency of the minor allele at rs188140481 in 4299 North American men including 1979 men with prostate cancer and 2320 healthy volunteers. We compared the clinicopathological features of prostate cancer between carriers and non‐carriers of the SNP. Results The rs188140481[A] SNP was present in 1.6% of the cohort; it was significantly more likely to be carried by men with prostate cancer than healthy controls (odds ratio 3.14; 95% confidence interval [CI] 1.85–5.35). After adjusting for age and PSA levels, carriers were found to be 6.73‐fold (95% CI 1.69–26.76) more likely to develop prostate cancer than non‐carriers. Age at diagnosis, frequency of a positive family history of prostate cancer, and biochemical recurrence rates were similar between SNP carriers and non‐carriers. Patients with the SNP had a proportionately higher frequency of stage ≥T2c disease (29.5% vs 20.1%; P = 0.13), Gleason ≥8 tumours (13.3% vs 6.5%; P = 0.10), and extracapsular extension (28.9% vs 18.8%; P = 0.12) compared with non‐carriers. Conclusions rs188140481[A] is a rare SNP that confers greater risk of prostate cancer compared with SNPs identified by genome‐wide association studies. Because of its low frequency, larger studies are needed to validate the prognostic significance of this locus, and associations with adverse pathology.